THE ANALYSIS OF STUDENTS' INTERNAL AND EXTERNAL ANXIETY IMPACT OF EARTHQUAKE VICTIMS IN STUDYING ENGLISH AT TAPALANG DISTRICT - Nur Amaliah Amaliah; Hasnawati Latief; Andi Bulkis Maghfirah Mannong (FKIP Unismuh Makassar, 2022)
This study has a main problem regarding the internal and external impacts of anxiety that affect students in carrying out English language learning due to the earthquake that hit West Sulawesi. The subjects of this study were students at SMAN 2 Tapalang. The method used is descriptive qualitative research that analyzed internal and external impact of anxiety faced by the students in learning due to the earthquake in West Sulawesi. This study used observation and interview as data collection instruments. In data analysis, the researcher used three steps, the first step is data reduction, the second step is data display and the last step is data verification.The results showed that there are two impacts that are felt by the students during the learning process due to the earthquake in Tapalang District, namely internal and external impacts. Internal impacts felt by the students included psychological conditions and psychological conditions. External impacts felt by the students namely from the impact of schools, families and communities.